Մարգար Խոջենց Երևանցու կյանքն ու գործունեությունը - Սահակյան, Քնարիկ
The article is dedicated to the life and work of Margar Khojents‘, a promi-nent representative of the Armenian Diaspora, orientalist, translator, and linguist. It is known that Margar Khojents‘ was born in Yerevan and lived many years in Smyrna, where he worked as a translator at the British Consulate. From the end of the 18th century, Khojents‘ lived in St. Petersburg, where he served as a collegiate councilor at the Imperial Court. He knew several European and Oriental languages, was engaged in literary translation and created his own works. Khojents‘ contribut-ed significantly to the Armenian book printing in Russia. In collaboration with Grigor Khaldaryan, Hovhannes Dolgoruky-Argutinsky, and the Lazarev family, he published his own and other authors’ works in Astrakhan, Nor Nakhijevan, and St. Petersburg. Khojents‘ was held in high esteem both at the Imperial Court and in the Armenian community. Yet, for the time being, his name is almost unknown. He died in 1820 in St. Petersburg at the age of 83. Статья посвящена жизни и творчеству Маркара Ходженца - переводчика, лингвиста, востоковеда, одного из ярких представителей армянской интеллигенции. Известно, что Маркар Ходженц родился в Ереване, жил в Смирне, где работал переводчиком в британском консульстве. В конце XVIII в. он переехал в Санкт-Петербург и был назначен на должность коллежского советника при Императорском дворе. Маркар Ходженц владел несколькими европейскими и восточными языками, делал литературные переводы, сочинял собственные произведения. Он внес большой вклад в дело армянского книгопечатания в России. В результате сотрудничества с Григором Халдаряном, Иваном Долгоруким-Аргутинским и при содействии семьи Лазаревых Маркар Ходженц подготовил к печати как собственные труды, так и произведения других авторов в Новой Нахичевани, Астрахани и Санкт-Петербурге. Его высоко ценили как в армянском обществе, так и при Императорском дворе, однако нашим современникам его имя почти неизвестно. Маркар Ходженц умер в С. Петербурге в 1820 г. в возрасте 83-х лет.
Keywords: Ձեռագրեր; Զմյուռնիա; Կենսագրություն